The Effect of Ticlopidine on Platelet Functions in Acute Myocardial Infarction - Knudsen, J Bjerre; Kjøller, E; Skagen, K; Gormsen, J (Thrombosis and Haemostasis, 1985)
A group of 43 consecutive patients with AMI were randomized to treatment with a novel platelet inhibitor, ticlopidine, or placebo in a double blind study. Treatment was started within 12 hr after onset of precordial pain. Patients who had taken drugs with known platelet inhibitory effect prior to the onset of therapy were excluded.Platelet survival time (PS) was measured 24–36 hr after onset of precordial pain and after 3 months of treatment in both groups. In the early phase of AMI CK-MB and ASAT were taken twice daily for estimation of infarction size. Platelet function, coagulation factors and fibrinolysis parameters were followed sequentially for 21 days and repeated after 3 months.In the placebo group a significant reduction in PS (5.62 ± 1.63 S. D. days) was measured in the acute phase of AMI compared to PS 3 months after infarction (8.03 ± 1.20 S.D. days). In the ticlopidine group PS was normal during the acute phase (8.35 ± 1.82 S.D. days). After 3 months of treatment PS was normal in both groups. During the first two weeks after AMI significant changes in coagulation parameters and fibrinolysis indicated an increased risk of thrombosis in both groups. These parameters were unaffected by the platelet inhibitory therapy. Estimated by peak CK-MB and ASAT, infarction size was significantly reduced in the ticlopidine group.
Keywords: Platelet survival; Ticlopidine; Acute myocardial infarction